2000
DOI: 10.1159/000055951
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Model of Benign External Hydrocephalus That Predicts a Predisposition towards Extra-Axial Hemorrhage after Minor Head Trauma

Abstract: Introduction: There is controversy over whether there exists a predisposition towards bleeding into the subdural space in infants with benign external hydrocephalus (BEH) or other enlargement of the extra-axial space (e.g. subdural hygroma). The presumed etiology implicates shear forces in over-stretching the extra-axial blood vessels. We have created a model of the intracranial space that approximates certain aspects of BEH. Using this model, we predict situations where children with BEH will bleed into the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 19 publications
2
48
1
Order By: Relevance
“…Papasian and Frim developed a simple mathematical model to demonstrate increasing vulnerability of bridging convexity veins to stretch and rupture with increasing depth of the subarachnoid space. 11 This model does not explain why hemorrhage from ruptured veins collects in the subdural space instead of the subarachnoid space. Nor does it explain collections that are predominantly CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Papasian and Frim developed a simple mathematical model to demonstrate increasing vulnerability of bridging convexity veins to stretch and rupture with increasing depth of the subarachnoid space. 11 This model does not explain why hemorrhage from ruptured veins collects in the subdural space instead of the subarachnoid space. Nor does it explain collections that are predominantly CSF.…”
Section: Discussionmentioning
confidence: 99%
“…12,14 Enlargement of the subarachnoid space may stretch and place increased strain on bridging veins, with resultant rupture and SDH formation. 7,13,29 This potential increased strain on bridging veins has been modeled mathematically 13 but is not universally accepted. 34 Membranes surrounding an aging subdural hematoma are highly vascularized and have been postulated to potentially allow rebleeding either spontaneously or with minimal trauma.…”
Section: Discussionmentioning
confidence: 99%
“…6 Some investigators have suggested that children with macrocrania and enlargement of the SS may be at increased risk for subdural hemorrhage (SDH) after minimal or no trauma. [7][8][9][10][11][12][13][14][15] A clinical dilemma often arises when subdural collections (SDC) are identified in children with enlarged SS because the identification of SDC in an infant without an appropriate traumatic history raises the concern for abusive head trauma (AHT). 3,12,16,17 The literature connecting enlarged SS and risk of SDC is based predominately on case reports or small case series.…”
mentioning
confidence: 99%
“…5,6 Our data suggest that the decision of whether to initiate anticoagulation for infants with venous thromboembolism should take into account this risk of intracerebral hemorrhage and the benefits of anticoagulation. This consideration is especially important in cases where there is comorbid cerebral hypoxicischemic injury, infection, or a metabolicgenetic abnormality that is likely to result in brain atrophy.…”
Section: Discussionmentioning
confidence: 93%